Oxidative stress and antioxidant vitamins in cataract patients - ., Ghazala; Ali, Syed Liaquat; Siddiqui, Jamil Ahmed; Khanam, Aziza; Memon, Saleh (International Journal of Research in Medical Sciences, 2019)
Background: In Pakistan age related vision disturbances are mainly due to cataract. Various studies have reported relationship of ocular lesion with senile changes and diabetes mellitus resulting in reduced quality of life due to vision. Oxidative stress is an important factor in the process of cataractogenesis. The pathogenesis of the cataract may involve decreased activity of antioxidant scavenging system which includes non-enzymatic natural antioxidants as biomolecules such as carotenoids and vitamins. So, it is planned to investigate the level of serum antioxidant vitamins in diabetic cataract patients and in non-diabetic cataract patients. Methods: The study was conducted at Biochemistry department, Al-Tibri Medical College Karachi from October 2016 to October 2017. Ninety pre diagnosed cataract patients were selected from Al-Ibrahim Eye Hospital Karachi 40 normal control subjects were selected from the same population with same socioeconomic group. The demographic data was analyzed. The random blood sugar, antioxidant vitamins (C, A and E) and malondialdehyde were analyzed in the blood sample of control and cataract patients. The data was analyzed by SPSS version 20. Results: There was no significant difference in the level of vitamin C, A, E and MDA between diabetic and non-diabetic cataract patients, but the blood levels of vitamins of control are higher as compared to the cataract patients. The level of MDA is significantly high in cataract patients as compared to control. Antioxidant vitamin E was negatively correlated with serum malondialdehyde in cataract patients. Conclusions: It is concluded that in diabetic and non-diabetic cataract low level of serum antioxidant vitamins may be a contributory factor for cataractogenesis.